Banning Weapons of Mass Destruction - Mattis, Frederick N. (London Praeger Security Internatioinal, 2009)
Discusses original principles for a treaty banning nuclear and chem-bio weapons worldwide. This book argues that a proposed new nuclear treaty, replacing today's inadequate 1968 Non-Proliferation Treaty, would demand unanimous accession by States which must be achieved before such a treaty enters into force.
Include Appendix and Index
Keywords: Nuclear arms control--International cooperation -- Nuclear disarmament--International cooperation -- Nuclear weapons--Government policy -- Weapons of mass destruction--Government policy -- Nuclear nonproliferation--International cooperation